Fresno County Women Lawyers Annual Dinner: Honoring Mary Louise Frampton - Watkins, Howard::::::::: (1989)
Joan Wilkie, Sandra Snyder, 2nd District Court of Appeal Presiding Judge Arleigh Woods and Jim Wilkie